Discovering Grade 9 students' metacognition in mathematical problem solving: A case study - Zhan, Jingye (Animo Repository, 2022)
Metacognition plays a significant role in succeeding in Mathematical problem-solving. The study is interested in discovering learners’ perspectives in dealing with mathematical problem-solving on metacognition through a case study. The study employed a qualitative descriptive research design. The Think Aloud Protocol was used to achieve elaborate data and to shed light on capturing the mental process of learners in dealing with Mathematics problem-solving. The participants consisted of six 9th Grade students (15-year-old) who are representatives of three diverse levels of problem-solving ability in Mathematics from a private school in Manila, the Philippines. Data was collected through problem-solving tasks paired with semi-structured interviews and video-recorded observations using Think-Aloud Protocols to explore learners’ metacognition when solving problems. All the processes under the data gathering were recorded carefully for documentation purposes. The essential findings based on content analysis and cross-case pattern techniques revealed that all six students have very high-level planning skills. However, the mid-level and low-level performers showed a low level of monitoring skill and evaluating skills. The students have a good foundation in declarative and procedural knowledge but must develop conditional knowledge under the metacognitive knowledge domain. Keywords: Metacognition, Metacognitive knowledge, Metacognitive regulation, Mathematics problem-solving, Think aloud protocols.